2019
DOI: 10.5539/jas.v11n10p98
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impeding Effective Crop Production in Ethiopia

Abstract: In the Ethiopia crop agriculture, pillar in balancing the food diet of the majority people, as a whole and the cereals specifically is facing serious and vast challenges which in turn affect the supply of food grains. Various research institutes in Ethiopia have revealed several factors which affect crop production over the past three decades, but their findings are not synthesized into a whole and difficult to access as such. This study attempts to review various existing research findings and present them ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Lacks of wide adaptive improved varieties are the major production problem in Ethiopia ( Yimer and Babege, 2018 ). In support of this argument, Merga and Haji (2019) reported that the challenges of farmers for improved crop use was less availability and inappropriately following the packages recommended by the researcher. According to the report of FAO (2011) , fewer than 5% of farmers had access to improved seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacks of wide adaptive improved varieties are the major production problem in Ethiopia ( Yimer and Babege, 2018 ). In support of this argument, Merga and Haji (2019) reported that the challenges of farmers for improved crop use was less availability and inappropriately following the packages recommended by the researcher. According to the report of FAO (2011) , fewer than 5% of farmers had access to improved seeds.…”
Section: Discussionmentioning
confidence: 99%
“…However, agricultural systems in the region are at subsistence level and production and productivity of food crops are low as compared to the crop potential. The most common factors are recurrent drought, degradation of natural resources, lack of appropriate technologies and low levels of input use (fertilizer, pesticide, improved seeds), weak institutional support, inadequate agricultural research and extension, pests, and constraints in market development ( Merga and Haji, 2019 ; Taffesse et al., 2012 ). However, production potentials and its factors vary across different agro-ecologies in the region.…”
Section: Introductionmentioning
confidence: 99%
“…They have suggested expansion of irrigated area to increase rice production. Merga & Haji (2019) has reviewed various existing research findings and identified most common factors of impeding crop production such as lack of more recently introduced improved seeds, initial capital for investment, loss of cropland, labour, pesticides, invasive alien species, farm storage techniques, methods of small scale irrigation, and religious and cultural challenges. From their study, it was understood that capital for investment, improved seeds, crop land, labour, irrigation are important factors of crop production.…”
Section: Theoretical Conceptmentioning
confidence: 99%
“…The total production from 12,429 ha of land was only 124,801 quartiles. The low production of garlic growth, yield, and yield-related traits was due to biotic and abiotic factors such as lack of high-yielding genotypes [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ], inappropriate organic and inorganic fertilizer [ 3 , 4 , 18 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ], inappropriate intra-row spacing [ 38 , 42 , 43 , [53] , [54] , [55] , [56] , 69 ], clove weight and size [ [57] , [58] , [59] , [60] ], watering [ [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ], mulching [ 70 , 71 ], disease [ 12 , 36 , 42 , [53] …”
Section: Introductionmentioning
confidence: 99%